The Dynamics of Ancient Empires - Morris, Ian.
1 online resource (400 pages)
Keywords: The Dynamics of Ancient Empires is designed to address the deficit in the comparative study of ancient empires in the western Old World, and to encourage dialogue across disciplinary boundaries by examining the fundamental features of the successive and partly overlapping imperial states that dominated much of the Near East and the Mediterranean in the first millennia BCE and CE.